Comparación en la eliminación de smear layer con el uso de diferentes irrigantes endodónticos, revisión bibliográfica - Montenegro Aguirre, Melanie Lizeth (2019)
Aim: develop a bibliographic review that allows knowing the properties of different irrigants used in endodontics and their combinations to make a comparison of these solutions and in this way to determine which of them produces greater dentinal smear removal. Among other objectives we have to define the use of each irrigator according to the pathology to be treated, to know the benefits of the smear layer elimination, to understand the differences of the endodontic irrigators for the smear layer elimination, to know irrigation methods and different tips of ultrasound that improve the smear layer elimination and know the chemical composition of the smear. Methodology: the bibliographic review is a compilation of recent and important information based on scientific articles that will allow the collection of information on the endodontic irrigators implemented for the elimination of smear layer that will allow an increase of knowledge in future generations. It is based on a statistical type material, which allows the combination and quantitative analysis of the results obtained in each study; obtained from reviews of literature, magazines and books through search strategies, information analysis, identification and selection of potential articles. Results: it was analyzed according to the literature that there is currently no single endodontic irrigator that allows the removal of smear layer, so it is necessary to implement a chelating solution, a sonic or ultrasonic irrigation method and a specific tip that reaches the entire length of the root canal that allows the greatest amount of smear layer removal. Conclusion: the bibliographic review allows determining that most of the investigated endodontic irrigators allow the elimination of smear layer, but some allow greater removal of the same. In turn, the elimination of this layer will depend on the knowledge of the professional and times of use of the irrigant, type of irrigant used, the combination of chelant used, the implementation of an irrigation method and the use of an ultrasound tip that allows to take the form of the conduit and eliminate the smear layer in the three thirds of the root canal.